Mifepristone inhibits IGF-1 signaling pathway in the treatment of uterine leiomyomas - Shen Q; Zou S; Sheng B; Zhao M; Sun LZ; Zhu X (Dove Medical Press, 2019)
Qi Shen1, Shuangwei Zou1, Bo Sheng1, Menghuang Zhao1, Lu-Zhe Sun2, Xueqiong Zhu1 1Department of Obstetrics and Gynecology, The Second Affiliated Hospital of Wenzhou Medical University, Wenzhou, People’s Republic of China; 2Department of Cell Systems and Anatomy, University of Texas Health Science Center at San Antonio, San Antonio, TX, USACorrespondence: Lu-Zhe SunDepartment of Cell Systems and Anatomy, University of Texas Health Science Center at San Antonio, San Antonio, TX, USAEmail sunl@uthscsa.eduXueqiong ZhuDepartment of Obstetrics and Gynecology, The Second Affiliated Hospital of Wenzhou Medical University, No. 109 Xueyuan Xi Road, Wenzhou, Zhejiang 325027, People’s Republic of ChinaTel +86 5 778 800 2796Fax +86 5 778 800 2560Email zjwzzxq@163.comPurpose: To investigate the role of IGF-1 signaling pathway in the treatment of uterine leiomyomas with mifepristone.Patients and methods: From October 2015 to December 2018, 50 patients with uterine leiomyoma were included in this study. Overexpression or siRNA of IGF-1 in primary human uterine leiomyoma cells were treated with or without mifepristone. MTT was used to evaluate cell viability in assays of cell proliferation and cytotoxicity. IGF-1 expression in the cells was measured with real-time RT-PCR and Western blotting and manipulated with lentivirus ectopic overexpression or siRNA silencing.Results: Inhibition of cell viability by mifepristone was found dependent on drug concentration and treatment time. IGF-1 and phosphorylation-ERK1/2 expression were decreased, while phosphorylation-AKT expression was increased after mifepristone treatment. IGF-1 significantly promoted cell growth, while IGF-1 knockdown and mifepristone showed synergistic inhibition effects on cell growth. The overexpression of IGF-1 reversed the inhibition of cell growth and ERK1/2 phosphorylation but showed no effect on AKT phosphorylation.Conclusion: Our study for the first time demonstrated that IGF-1 signaling via ERK1/2 appears to be an important target of mifepristone in the treatment of uterine leiomyomas, which may provide a new approach to avoid leiomyoma re-growth after cessation of mifepristone.Keywords: uterine leiomyomas, mifepristone, IGF-1, signal pathway